A Semantic Analysis (look) on the Book Al.... Based on Fazel Sameraee’s Views - Mousa Arabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Due to its unique features and emergence of new concepts and meanings after the revelation of Quran, Arabic language has been the center of attention by the semantic experts from the beginning until the contemporary era. Among contemporary linguists and syntax analysts, Fazel Sameraii has also written some works, one of which is the book “Al-jomlat ol-Arabia val-Mani”. In this study, it has been tried to investigate and analyze this book in terms of both form and content. The results of the study show that this book is in line with the Islamic approaches, and the writer also has control of the authentic resources. In understanding Arabic sentences, Sameraii has used constructivist semantics. He also exploited role-oriented linguistics by making use of Maqam and style symmetry. Although he could not propose a comprehensive approach to the role of symmetrical relationships in semantics like Tamam Hasan, who developed the theory of symmetrical correlation, he mentioned the role of each symmetry in its own place, which was a success. However, in terms of form, the book lacks rudimentary and didactic tools. As well as the strengths, some suggestions have been provided concerning the weak points.